How Is Your Cleaning Behavior? House Dust Mites and Its Relationship to Allergic Rhinitis - Kahfi Karunia Ilahi; Erma Sulistyaningsih; Erfan Efendi (Al-Sihah : The Public Health Science Journal, 2021)
The main allergen of allergic rhinitis is house dust mites (HDM), that often found in humid room conditions and furnitures. The health behaviour consists of knowledge, attitude, and practice is closely related to the occurrence of disease including allergic rhinitis. One of the methods to screen allergic rhinitis is the score for allergic rhinitis (SFAR) questionnaire. This study aimed to determine the relationship between behaviour (knowledge, attitude, and practice) on house dust mites and the SFAR score. This was an analytical observational study on female population age 17-34 years old in Jember District. As many as 141 respondents were selected using the purposive sampling technique based on inclusion and exclusion criteria. Data were collected using an online behaviour questionnaire and the SFAR. The primary data were analyzed statistically by chi-square test with a significance value of p <0.05. The results showed that 46 respondents (32.62%) had an SFAR score > 7, indicated allergic rhinitis symptoms. The majority of respondents (76 people or 54%) had sufficient knowledge about HDM, as many as 132 respondents (93.62%) had a good attitude towards HDM and 94 respondents (66.67%) had a good practice towards HDM. Statistical analysis showed that there was a relationship between knowledge, attitude, and practice on HDM and the SFAR score, each with the value of p = 0.000. In conclusion, good knowledge, attitude, and practice to HDM would decrease the HDM population resulting in reduce of allergic rhinitis risk, that could be screened by SFAR.